ASME 2012 Summer Bioengineering Conference, Parts a and B 2012
DOI: 10.1115/sbc2012-80293
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of TKR Function Using Specimen Specific Robotically Calibrated Knee Models

Abstract: Passive knee kinematics and kinetics following total knee replacement (TKR) are dependent on the topology of the component joint surfaces as well as the properties of the passive soft tissue structures (ligaments and capsule). Recently, explicit computer models have been used for the prediction of knee joint kinematics based on experimental investigations [1]. However, most of these models replicate experimental knee simulators [2], which simulate soft tissue structures using springs or elastomeric structures.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Our findings in the MC group differ from the previous literature showing that, after sacrifice of the PCL, many TKA designs showed significant posterior tibial translation compared to normal knees. 32 The current authors justified this finding according to the specific more posterior dwell point on the MC insert when compared to CR and PS polyethylene (PE) designs 33 : in fact, in the kneeling x-ray, we could detect that the insert stays congruent with the medial femoral condyle in a more anterior position thanks to the 1/1 ratio between the J-curve shaped condyle and the fully congruent insert. In addition to this, even though the tibia and the baseplate showed a greater posterior draw when compared to PS, the MC insert might diminish the amount of shear forces on the PE and by that count avoid conflict between the elevated posterior lip of the insert and the posterior cortex of the femur during high flexion; it has also been demonstrated that more conforming surfaces could diminish the risk of degradation of the PE.…”
Section: Discussionmentioning
confidence: 69%
“…Our findings in the MC group differ from the previous literature showing that, after sacrifice of the PCL, many TKA designs showed significant posterior tibial translation compared to normal knees. 32 The current authors justified this finding according to the specific more posterior dwell point on the MC insert when compared to CR and PS polyethylene (PE) designs 33 : in fact, in the kneeling x-ray, we could detect that the insert stays congruent with the medial femoral condyle in a more anterior position thanks to the 1/1 ratio between the J-curve shaped condyle and the fully congruent insert. In addition to this, even though the tibia and the baseplate showed a greater posterior draw when compared to PS, the MC insert might diminish the amount of shear forces on the PE and by that count avoid conflict between the elevated posterior lip of the insert and the posterior cortex of the femur during high flexion; it has also been demonstrated that more conforming surfaces could diminish the risk of degradation of the PE.…”
Section: Discussionmentioning
confidence: 69%